SAGO STARCH AS FERMENTATION MEDIUM FOR PRODUCTION OF AND SUBSTRATE FOR CARBOHYDRATE ENZYMES - Karossi, A.T. (Teknologi Indonesia, 2009)
It is well known that sago starch extracted from sago palm (Metroxylon sp.) is abundantly available especially in eastern part of Indonesia. On the other hand, amylases and related enzymes are recognized as the most important industrial enzymes, specifically in the field of food industries. Therefore, fermentation experiments were carried out to utilize sago starch as medium component to produce extracellular alpha amylase and glucoamylase as well as glucose isomerase, which is the later being an intracellular enzyme. Aspergillus oryzae was selected fermenting microorganism to produce the extracellular alpha amylase and intracellular glucose isomerase, while Rhizopus oryzae was for producing extracellular glucoamylase. The investigation included optimum fermentation process condition for enzymes production, both in Ehrlenmeyer shaken flasks and stirred tank fermentors, then was followed by isolation with ammonium sulfate fractionation, concentration employing polysulfon membrane, purification with chromatography technique, and characterization of the enzymes. In fact, sago starch could function as a medium component in fermentation producing amylases as well as a substrate for the enzymes. The biomass of the Aspergillus contained glucose isomerase activity. Experiments with fermentor indicated that alpha amylase was best produced at agitation rate of 500 rpm, while glucoamylase was at 350 rpm, both at 1.5 vvm aeration. The SDS-PAGE of the purified enzymes found that the alpha amylase and glucoamylase had molecular weights of 53 and 36 kDalton respectively, while the glucose isomerase indicated to have two subunits with molecular weight each of 55 and 60 kDalton. As a substrate for alpha amylase and glucoamylase, sago starch exhibited higher affinity compared with arenga, corn, and cassava starches although it was still inferior to soluble starch.